Dose-response technique combined with stable isotope tracing for drug metabolite profiling by using high-resolution mass spectrometry - Lin, I-Shou; Chuang, Chia-Ying Anderin; Shih, Chia-Lung (Frontiers in Pharmacology, 2023)
Background: Mass spectrometry metabolomics-based data-processing approaches 22 have been developed for drug metabolite profiling. However, existing approaches 23 cannot be used to comprehensively identify drug metabolites with high efficacy. 24Methods: Herein, we propose a two-stage data-processing approach for effective and 25 comprehensive drug metabolite identification. The approach combines dose-26 response experiments with stable isotope tracing (SIT). Rosiglitazone (ROS), 27 commonly used to treat type 2 diabetes, was employed as a model drug. 28In the first stage of data processing, 1071 features exhibited a dose-response 29 relationship among 22597 features investigated. In the second stage, these 1071 30 features were screened for isotope pairs, and 200 features with isotope pairs were 31 identified. In time-course experiments, a large proportion of the identified features 32 (69.5%: 137 out of 200 features) were confirmed to be possible ROS metabolites. We 33 compared the validated features identified using our approach with those identified 34 using a previously reported approach [the mass defect filter (MDF) combined with SIT) 35 and discovered that most of the validated features (37 out of 42) identified using the 36 MDF-SIT combination were also successfully identified using our approach. Of the 143 37 validated features identified by both approaches, 74 had a proposed structure of an 38 ROS-structure-related metabolite; the other 34 features that contained a specific 39 已刪除: -based…metabolomics-based data …ata-processing 120 approaches have been developed for drug metabolite 121 profiling. However, the previously reported…xisting 122 approaches cannot be used for …o comprehensively identify 123 drug metabolites identification 124 ... [1] 已刪除: d…a two-stage data …ata-processing approach for 125 effective and comprehensive drug metabolite identification. 126 The approach by…combinesing…a …ose-response 127 experiments and …ith stable isotope labelled …racing (SIT).128 Rosiglitazone (ROS), is …ommonly used to treat type 2 129 diabetes, and …as adopted …mployed as a model drug in this 130 study… A two-stage data processing approach by combining 131 a dose-response experiment and isotope-labelled tracing 132 was developed for metabolite identification.